2021
DOI: 10.3389/fcvm.2021.704251
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Echocardiographic Non-invasive Myocardial Work Indices and Myocardial Fibrosis in Patients With Dilated Cardiomyopathy

Abstract: Objectives: To analyze the association between global myocardial work indices evaluated by non-invasive left ventricular (LV) pressure-strain loop (PSL) and LV myocardial fibrosis in patients with dilated cardiomyopathy (DCM).Methods: A total of 57 patients with DCM were included in this prospective study. Global work index (GWI), global constructive work (GCW), global wasted work (GWW), global work efficiency (GWE) and global longitudinal strain (GLS) were measured using LVPSL. LV volumes and LV ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…57 Dilated cardiomyopathy GWI, GCW, and GWE are better predictors of fibrosis on MRI than GLS. 62 GWI and GCW found to be predictors of all-cause mortality and need for LV assist device implantation/transplantation. 63 Cardio-oncology Myocardial work indices associated with a higher probability of concurrent CTRCD than GLS in small subset of patients with >21 mm Hg systolic blood pressure reduction and a GLS change (<3.3%).…”
Section: Aortic Regurgitationmentioning
confidence: 93%
“…57 Dilated cardiomyopathy GWI, GCW, and GWE are better predictors of fibrosis on MRI than GLS. 62 GWI and GCW found to be predictors of all-cause mortality and need for LV assist device implantation/transplantation. 63 Cardio-oncology Myocardial work indices associated with a higher probability of concurrent CTRCD than GLS in small subset of patients with >21 mm Hg systolic blood pressure reduction and a GLS change (<3.3%).…”
Section: Aortic Regurgitationmentioning
confidence: 93%
“…Clinical assessment of LV systolic function in CAD provides a more accurate new indicator. PSL has also played an important role not only in the field of cardiology, but also in dilated cardiomyopathy, 52,53 hypertrophic cardiomyopathy, 54,55 right ventricular cardiomyopathy, 56 hypertension, 52,57 and the evaluation of cardiac synchronization therapy. 13,58,59 Changes in LVMW with exercise can also be an effective means of quantifying myocardial contractile reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial work is another novel parameter of transthoracic echocardiography, reflecting the stroke work through pressure-strain loop by incorporating deformation and afterload information of the left ventricle ( 70 ). Recent studies indicated that parameters of myocardial work were associated with CMR findings of fibrosis and global constructive work (GCW) showed a better ability to predict myocardial fibrosis compared with GLS ( 71 , 72 ).…”
Section: Detection: Laboratory Biomarkers and Imaging Techniquesmentioning
confidence: 99%